The Impact of Motivation And Training on Performance of Tourism Managers - Iskandar, iskandar; Yapentra, Arhipen; Putra, Eka (ADPEBI, 2022)
This study aims to determine the effect of work motivation and training on the performance of tourism object managers. This research is a quantitative research using SPSS 25 to process data. This research was conducted on tourism objects in Kampar Regency, Riau Province, Indonesia. The sampling technique used is simple random sampling technique. The sample was calculated using the Slovin formula where 48 respondents were selected. The results showed that from the results of the partial test (t test), there were two variables, namely work motivation and training had a positive and significant effect on the performance of tourism object managers. also that 52.8% the influence of independent variables (motivation and training) on ​​the performance of managers is 52.8% and the remaining 47.2% is influenced by other variables not examined.